1997
DOI: 10.1016/s0092-8674(00)80366-9
|View full text |Cite
|
Sign up to set email alerts
|

RIGUI, a Putative Mammalian Ortholog of the Drosophila period Gene

Abstract: The molecular components of mammalian circadian clocks are elusive. We have isolated a human gene termed RIGUI that encodes a bHLH/PAS protein 44% homologous to Drosophila period. The highly conserved mouse homolog (m-rigui) is expressed in a circadian pattern in the suprachiasmatic nucleus (SCN), the master regulator of circadian clocks in mammals. Circadian expression in the SCN continues in constant darkness, and a shift in the light/dark cycle evokes a proportional shift of m-rigui expression in the SCN. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
385
3
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 631 publications
(426 citation statements)
references
References 44 publications
35
385
3
3
Order By: Relevance
“…Even though all three mPer isoforms cycle at both the mRNA and the protein levels in the SCN, mPer1 also shows region-specific and SCN-independent expression rhythm (von Gall et al, 2001;Sun et al, 1997;Iijima et al, 2002). Since SCN is thought to coordinate and regulate behavioral clocks in mammals, only a few studies have explored the SCN-independent rhythms of clock genes in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Even though all three mPer isoforms cycle at both the mRNA and the protein levels in the SCN, mPer1 also shows region-specific and SCN-independent expression rhythm (von Gall et al, 2001;Sun et al, 1997;Iijima et al, 2002). Since SCN is thought to coordinate and regulate behavioral clocks in mammals, only a few studies have explored the SCN-independent rhythms of clock genes in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatic oscillator is centered on a pair of transcriptional activators, BMAL1 (also named Mop3) (Bunger et al, 2000;Hogenesch et al, 1998) and CLOCK (Gekakis et al, 1998;King et al, 1997) and two classes of repressors of the Period (Per) Shearman et al, 1997;Sun et al, 1997;Tei et al, 1997) and Cryptochrome (Cry) gene families (Griffin et al, 1999;Kume et al, 1999;van der Horst et al, 1999;Vitaterna et al, 1999) (Fig. 2).…”
Section: Transcriptional Network Of the Hepatic Circadian Oscillatormentioning
confidence: 99%
“…Recent molecular dissection has revealed that the feedback loop is the basic concept of the circadian oscillator, conserved across the species from Neurospora and Drosophila to mice (Dunlap 1998a,b;Schibler 1998;Young 1998). A mammalian clock gene period consists of a family containing three members (mPer1, mPer2 and mPer3) (Shearman et al 1997;Sun et al 1997;Tei et al 1997;Takumi et al 1998a,b). The transcription of mPer1 is activated by the binding of the CLOCK/BMAL1 hetero-complex, both of which are bHLH-PAS proteins, to the E-boxes in the promoter region of mPer1 (Gekakis et al 1998).…”
Section: Introductionmentioning
confidence: 99%